In memory of Alexander Suvorov - Editorial board (Вопросы атомной науки и техники, 2005)
Alexander Leonidovich Suvorov, the director of the State Science Center of Russian Federation - Institute of Theoretical and Experimental Physics (ITEP) suddenly passed away on 18 June 2005. 18 июня 2005 года скоропостижно скончался директор ФГУП ГНЦ РФ «Институт теоретической и экспериментальной физики» Суворов Александр Леонидович.